Pattern Recognition 7th Asian Conference, ACPR 2023, Kitakyushu, Japan, November 5-8, 2023, Proceedings, Part II - Lu, Huimin; Blumenstein, Michael; Cho, Sung-Bae.; Liu, Cheng-Lin.; Yagi, Yasushi; Kamiya, Tohru (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This three-volume set LNCS 14406-14408 constitutes the refereed proceedings of the 7th Asian Conference on Pattern Recognition, ACPR 2023, held in Kitakyushu, Japan, in November 2023. The 93 full papers presented were carefully reviewed and selected from 164 submissions. The conference focuses on four important areas of pattern recognition: pattern recognition and machine learning, computer vision and robot vision, signal processing, and media processing and interaction, covering various technical aspects.
artificial intelligence -- computer networks -- computer science -- computer systems -- computer vision -- databases -- education -- engineering -- image analysis -- image processing -- image segmentation -- internet learning -- machine learning -- mathematics -- neural networks -- object recognition -- pattern recognition semantics -- signal processing.
Keywords: Artificial intelligence; Application software; Pattern recognition systems; Artificial Intelligence; Computer and Information Systems Applications; Automated Pattern Recognition